2002
DOI: 10.1177/03635465020300020901
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring Muscle Strain Recurrence and Strength Performance Disorders

Abstract: We determined the frequency of strength disorders in 26 athletes with a history of hamstring muscle injury and recurrent strains and discomfort. We also assessed the effectiveness of rehabilitation to correct muscle performance. After concentric and eccentric isokinetic assessment, 18 athletes were found to have strength deficits, as determined by statistically selected cutoffs of peak torque, bilateral differences, and the flexors/quadriceps ratio. The discriminating character of the eccentric trial was demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
379
6
24

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(419 citation statements)
references
References 40 publications
10
379
6
24
Order By: Relevance
“…Bilateral asymmetries of more than 10% have been reported to pose an increased risk of injury to football players [21]. With regards to bilateral imbalances in female collegiate athletes, it has been suggested that when a difference of 15% or more exists on either side of the body, the likelihood of sustaining an injury to the lower extremities increases [22].…”
mentioning
confidence: 99%
“…Bilateral asymmetries of more than 10% have been reported to pose an increased risk of injury to football players [21]. With regards to bilateral imbalances in female collegiate athletes, it has been suggested that when a difference of 15% or more exists on either side of the body, the likelihood of sustaining an injury to the lower extremities increases [22].…”
mentioning
confidence: 99%
“…4 An etiologic risk factor commonly attributed to the high incidence of thigh strain injuries is poor eccentric muscular strength. 5,6 The temporal pattern of injury during match play also indicates that fatigue might be a factor. 2 In English professional soccer players, 47% of match-play hamstrings strains were incurred during the final 15 minutes of each half.…”
mentioning
confidence: 99%
“…However, it seems that fatigue of only one of the limbs alters this common command and dissociating the command for both limbs (1) . In practical terms, training, as well as the familiarization to tasks, may reduce the bilateral strength deficit minimizing the asymmetry, especially at fatiguing conditions, in which the control dissociation may modify the overload between limbs, since tasks which present asymmetry between limbs are more prone to injuries during physical performance (30)(31)(32)(33)(34)(35)(36) .…”
Section: Asymmetryindices (%) Dominantmentioning
confidence: 99%